Desalination Engineering : Planning and Design - Voutchkov, Nikolay (McGraw-Hill's AccessEngineeringLibrary., 2013)
This book provides detailed background information on the planning and engineering of brackish and seawater desalination projects for municipal water supply. While it includes a brief overview of key widely used desalination technologies, it focuses on reverse osmosis (RO) desalination, which at present is the most widely used technology for the production of freshwater from saline water sources.